2016
DOI: 10.1038/srep31138
|View full text |Cite
|
Sign up to set email alerts
|

Rapid flow cytometric measurement of protein inclusions and nuclear trafficking

Abstract: Proteinaceous cytoplasmic inclusions are an indicator of dysfunction in normal cellular proteostasis and a hallmark of many neurodegenerative diseases. We describe a simple and rapid new flow cytometry-based method to enumerate, characterise and, if desired, physically recover protein inclusions from cells. This technique can analyse and resolve a broad variety of inclusions differing in both size and protein composition, making it applicable to essentially any model of intracellular protein aggregation. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(82 citation statements)
references
References 20 publications
1
81
0
Order By: Relevance
“…We also describe the use of the rapid flow cytometry technique FloIT 13 to quantify seeding and co-aggregation of proteins expressed in 2 separate populations of cells. In previous coculture experiments using SH-SY5Y (human neuroblastoma) cells, it was shown that TDP-43 can transfer between cells and that phosphorylated TDP-43 aggregates can be released from donor cells and taken up into recipient cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also describe the use of the rapid flow cytometry technique FloIT 13 to quantify seeding and co-aggregation of proteins expressed in 2 separate populations of cells. In previous coculture experiments using SH-SY5Y (human neuroblastoma) cells, it was shown that TDP-43 can transfer between cells and that phosphorylated TDP-43 aggregates can be released from donor cells and taken up into recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…FloIT can quantify the proportion of inclusions containing 2 different proteins fused to distinct fluorescent protein tags. 13 Here we took advantage of this and quantified the proportion of inclusions that contained both TDP-43…”
Section: Tdp-43mentioning
confidence: 99%
See 3 more Smart Citations